Pharmacopoeial Standards and Specifications for Pharmaceutical Oral Liquid Preparations - Md. Sahab Uddin; Abdullah Al Mamun; Nahia Akter; Md. Shahid Sarwar; Mamunur Rashid; Md. Shah Amran (Archives of Current Research International, 2016)
Quality control is an essential operation of the pharmaceutical industry. It is the monitoring process which encompassing specifications, inspections, analysis and recommendations. The appropriate design and formulation of a dosage form requires discretion of the physical, chemical and biological characteristics of active pharmaceutical ingredients (APIs) and inactive pharmaceutical excipients (IPIs) to be used in formulating the pharmaceutical. The drug and others pharmaceutical materials utilized must be compatible with one another to produce a drug product that is stable, efficacious, potent, palatable, easy to administer and well tolerated. The quality of any drug in dosage form depends on its safety, potency, efficacy, stability, patient acceptability and regulatory compliance. In order to claim the pharmaceutical oral liquid preparations as quality drugs it must satisfy the aforementioned criteria. To conform the requirements of pharmaceutical oral liquids during manufacturing, in-process quality control (IPQC) tests are done as per specifications with a view to remove error or if necessary to adjust the process. The quality of final products depends on finished product quality controls (FPQC) test. So the quality of pharmaceutical oral liquids is strongly related to IPQC and FPQC tests. The purpose of this study is to focus on the different in-process and finished products quality control tests for pharmaceutical oral liquid preparations according to pharmacopoeias.